Legal History, Institutions and Banking System Development in Africa - Samuel Mutarindwa; Dorothea Schäfer; Andreas Stephan (Global Labor Organization (GLO), 2020)
This paper links banking systems development to the colonial and legal history of African countries. Specifically, we investigate the impact of differing legal traditions on the development of existing investor and creditor protection, and on African banking systems. Based on a sample of 40 African countries from 2000 to 2016, our empirical findings show a significant dependence of current financial institutions on the legal origin and the colonization type. Findings also reveal that current legal financial institutions are not the major determinants of banking system development, whereas institutional and regulatory quality significantly matter for banking system development in both common and civil law countries. Strong creditor rights reduce the cost of banking in African countries.
Keywords: G21; G38; G39; K15; K40; 330; Legal origins; colonial history; financial institutions; banking systems; Hausman-Taylor estimation